"Taking the Temperature of the Room": How Political Campaigns Use Social Media to Understand and Represent Public Opinion. Issue Volume 84:Issue S1(2020)Special Issue (15th July 2020) - McGregor, Shannon C
Abstract: For most of the twentieth century, public opinion was nearly analogous with polling. Enter social media, which has upended the social, technical, and communication contingencies upon which public opinion is constructed. This study documents how political professionals turn to social media to understand the public, charting important implications for the practice of campaigning as well as the study of public opinion itself. An analysis of in-depth interviews with 13 professionals from 2016 US presidential campaigns details how they use social media to understand and represent public opinion. I map these uses of social media onto a theoretical model, accounting for quantitative and qualitative measurement, for instrumental and symbolic purposes. Campaigns' use of social media data to infer and symbolize public opinion is a new development in the relationship between campaigns and supporters. These new tools and symbols of public opinion are shaped by campaigns and drive press coverage (McGregor 2019 ), highlighting the hybrid logic of the political media system (Chadwick 2017 ). The model I present brings much-needed attention to qualitative data, a novel aspect of social media in understanding public opinion. The use of social media data to understand the public, for all its problems of representativeness, may provide a retort to long-standing criticisms of surveys—specifically that surveys do not reveal hierarchical, social, or public aspects of opinion formation (Blumer 1948 ; Herbst 1998 ; Cramer 2016 ). This model highlights a need to explicate what can—and cannot—be understood about public opinion via social media.